2019
DOI: 10.1186/s13000-019-0911-4
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1298 is downregulated in non-small cell lung cancer and suppresses tumor progression in tumor cells

Abstract: Background: MicroRNAs (miRNAs) have been reported to serve pivotal roles in tumorigenesis. This study sough to assess the expression and clinical significance of microRNA-1298 (miR-1298) in patients with non-small cell lung cancer (NSCLC), and explore the functional role of miR-1298 in tumorigenesis. Methods: One hundred and twenty-one NSCLC patients were recruited in this study. The expression of miR-1298 was estimated using quantitative real-time PCR. Kaplan-Meier survival curves and Cox regression analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…25 A recent study by Du et al also demonstrated that the decreased expression of miR-1298 served as a biomarker in NSCLC prognosis. 26 Given the abnormal expression of miR-374b-5p in NSCLC tissues, the relationship between miR-374b-5p and the 5-year survival information was analyzed in NSCLC patients. The survival curves indicated that patients with low miR-374b-5p expression had a shorter survival time, and the Cox regression analysis revealed that miR-374b-5p was an independent prognostic indicator for patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…25 A recent study by Du et al also demonstrated that the decreased expression of miR-1298 served as a biomarker in NSCLC prognosis. 26 Given the abnormal expression of miR-374b-5p in NSCLC tissues, the relationship between miR-374b-5p and the 5-year survival information was analyzed in NSCLC patients. The survival curves indicated that patients with low miR-374b-5p expression had a shorter survival time, and the Cox regression analysis revealed that miR-374b-5p was an independent prognostic indicator for patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…10 Another research confirmed the downregulation of miR-1298 in non-small cell lung cancer and its suppressive role in cancer phenotypes. 11 In this study, miR-1298-5p was significantly downregulated in BC tissue samples, and the upregulation of miR-1298-5p significantly impaired cell phenotypes such as the viability, proliferation, colony formation, migration, and adhesion abilities of BC cells. For this reason, we speculated that miR-1298-5p could suppress BC growth.…”
Section: Discussionmentioning
confidence: 56%
“…It was uncovered in one research that miR-1298-5p played an anti-tumor role in KRAS oncogene-induced tumor growth in vivo and in vitro 10 Moreover, miR-1298 was demonstrated to be downregulated in patients with non-small cell lung cancer, thereby prolonging their survival time. 11 Although the investigation of the effect of miR-1298-5p on BC cells is still limited, it is hypothesized that miR-1298-5p might act as an anti-tumor miRNA in BC based on the previous studies that explored the impact of miR-1298-5p on other cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many miRNAs have been identified as prognostic biomarkers for NSCLC [28]. miR-1298 was found by Du et al to be aberrantly expressed in NSCLC, and aberrant miR-1298 can be used as a prognostic biomarker for NSCLS patients [29]. As a novel biomarker, miR-1231 has been considered as a promising prognostic factor for cancer.…”
Section: Discussionmentioning
confidence: 99%